Ultimate strength formulation of stiffened panels under in-plane compression or tension with cracking damage - Zareei, Mohammad Reza; Iranmanesh, Mehdi (Journal of Naval Architecture and Marine Engineering, 2018)
The aim of the present study is to develop closed-form formulations for predicting the ultimate compressive and tensional strength of stiffened steel panels with crack damages. First, a numerical database is generated. This database includes the ultimate strength levels of stiffened steel panels with cracks subjected to axial compressive or tensile loads. It was carried out with a series of nonlinear FEM analyses by varying the size of crack damage. In the following sections, regression analysis is used for deriving the empirical formulations. The results of the present paper can be used for the reliability and risk assessment of structures, including stiffened steel panels with cracks.